Qualitative evaluation study of urban shared spaces in New Zealand. (January 2016) - Karndacharuk, Auttapone; Wilson, Douglas J.; Dunn, Roger C.M.
Highlights: This paper investigated the qualitative aspects of shared spaces using on-street perception and expert interview surveys. The Median Perception Rating (MPR) was used as the main performance measure. The on-street perception survey results generally confirmed that the shared space schemes performed positively. The statistical analysis highlighted the interconnection between the five performance measures. The shared spaces outperformed the control site of O'Connell Street with respect to the 'Place, Pedestrian and Economic' measures. The results of the specialist interview surveys provided an insight into the key attributes of shared space design and operation. Abstract: This paper presents the findings of a qualitative analysis using on-street perception and expert interview surveys of city centre streets that have been transformed into shared spaces in Auckland, New Zealand. The principal purpose was to investigate how well the shared streets performed, especially in relation to movement, access and place functions. The shared space sites at the Elliott, Lorne and Fort Street areas were measured against the performance criteria of Placemaking, Pedestrian Focus, Vehicle Behaviour Change, Economic Impetus and Safety for all users. On-street perception surveys totalling 360 responses (120 per site) were used in this study, together with an additional set of 40 responses from a survey of a control site in O'Connell Street that remained as a traditional street. Fifteen professionals with background in transportation and urban planning participated in semi-structured expert interviews. The main results of the Median Perception Ratings from the on-street surveys confirmed that the shared spaces generally performed positively. The statistical analysis revealed that the performance criteria of 'Pedestrian' and 'Safety' had a commanding influence over the other performance measures, and with the interconnectivity of the five objectives the perceived success of the urban shared spaces.